Incidence of Various Types of Gallstones in Association with Age - Faiz Ur Rahman, Khawar Iqbal, Mohammad Shoaib Khan, Lekhraj Mal, Muhammad Attique Sadiq, Khalil-Ur-Rehman (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Gallstones are responsible for many hospitalizations and surgical interventions in our local population. Our main goal was to evaluate the relationship between age and gallstones as a risk factor in our local population. Methods: Cross-sectional study of all cholecystectomy patients with prior informed consent was conducted in the department of Surgery at Sheikh Khalifa Bin Zaid Hospital (PGMI), Quetta and Bacha Khan Medical Complex, Swabi for the duration of 06 months from 15th March 2021 to 15th August 2021. The stones are divided into 3 groups according to their colour: light yellow and whitish like a cholesterol stone, black and black-brown like a pigment stone, and laminated brownish or greenish yellow as mixed stones. The collected data was statistically processed using SPSS version 21. The types of stones were correlated with the age groups of the patients using the student’s test and / or the Chi-square test as appropriate. The confidence level was defined as 95% CI and p values ​​below 0.05 were considered statistically significant. Results: The study included 100 patients 14(14%) men and 86 (86% women) with a female to male ratio of 13.2: 1, chi-square = 1190.70, p < 0.0001 and their mean age was 46.2 years (SD ± 9.4) (Range, 30 to 75 years). The most common pigment stones were found in 44 (44%). The highest incidence of gallstones was found in the age groups 41-50 and 31-40, 44% and 26%, respectively (p <0.05). Conclusion: From the study it can be concluded that age has an influence on the occurrence of gallstone disease.